A relative clause analysis of event existential constructions in Aklanon - Wellstood, Zachary (Glossa (London), 2022)
This study is the first to document and analyze the ‘event existential construction’ (EEC) in Aklanon (AKL), an understudied Central Philippine language. In EECs, the apparent correlation between Philippine-type voice and nominal case appears to break down. However, I argue that the ‘case-cleaving effect’ of EECs is superficial. I argue for an analysis wherein the existential maj selects a relative clause as its complement and allows optional possessor raising of a relative- clause-external agent, which obligatorily controls a DP-internal PRO, to topic position, producing the case-cleaving effect. This study presents a typologically unusual type of obligatory DP control and contributes to a richer understanding of cross-linguistic variation in Philippine languages, while allowing us to maintain the robust generalization that Philippine-type voice is correlated with the argument role of the topic-marked nominal.